2002
DOI: 10.1073/pnas.022240299
|View full text |Cite
|
Sign up to set email alerts
|

Recombinatoric exploration of novel folded structures: A heteropolymer-based model of protein evolutionary landscapes

Abstract: The role of recombination in evolution is compared with that of point mutations (substitutions) in the context of a simple, polymer physics-based model mapping between sequence (genotype) and conformational (phenotype) spaces. Crossovers and point mutations of lattice chains with a hydrophobic polar code are investigated. Sequences encoding for a single ground-state conformation are considered viable and used as model proteins. Point mutations lead to diffusive walks on the evolutionary landscape, whereas cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 51 publications
4
97
1
Order By: Relevance
“…Because the surface-core ratio of folded structures on the 2D square lattice with chain lengths approximately 16 is similar to the surface-core ratio of 3D folded structures with chain length approximately 150 [317], the energetics of short-chain 2D HP models should bear resemblance to that of real proteins with approximately 100 amino acid residues. Second, as has been argued [324], although the simple potentials of the HP model and its two-letter variants, and for that matter even 20-letter lattice potentials, are not sufficient to capture more detailed thermodynamic [325] and/or kinetic [326] properties of protein folding, the HP potential may still provide a useful caricature of the mapping between sequence and folded structure of real globular proteins because of the 'consistency principle' [327] or 'principle of minimal frustration' [328]. These principles stipulate consistency or near-consistency among various energy terms that contribute to the stability of natural proteins.…”
Section: Model Interactions and Their Biophysical Basismentioning
confidence: 99%
See 1 more Smart Citation
“…Because the surface-core ratio of folded structures on the 2D square lattice with chain lengths approximately 16 is similar to the surface-core ratio of 3D folded structures with chain length approximately 150 [317], the energetics of short-chain 2D HP models should bear resemblance to that of real proteins with approximately 100 amino acid residues. Second, as has been argued [324], although the simple potentials of the HP model and its two-letter variants, and for that matter even 20-letter lattice potentials, are not sufficient to capture more detailed thermodynamic [325] and/or kinetic [326] properties of protein folding, the HP potential may still provide a useful caricature of the mapping between sequence and folded structure of real globular proteins because of the 'consistency principle' [327] or 'principle of minimal frustration' [328]. These principles stipulate consistency or near-consistency among various energy terms that contribute to the stability of natural proteins.…”
Section: Model Interactions and Their Biophysical Basismentioning
confidence: 99%
“…The latter observation may bear on the question of whether the currently known set of globular protein folds is nearly complete in its coverage of all physically possible compact folds, as discussed in §3.1 [286][287][288][289][290], but one has to also keep in mind that the HP model interaction potential is less heterogeneous, and thus entails fewer encodable structures, than model potentials that contain repulsive interactions or otherwise more heterogeneous interactions [158,322,323]. Fourth, the 2D HP lattice model provides sequences that act like evolutionary bridges [161, 178,204,239,299] (see §3.5), encode for autonomous folding units [292,316,324], and exhibit homology-like behaviours [295], all similar to properties observed in real proteins. Two likely physical reasons underlie the similarity between the sequence -structure mapping of the 2D HP model and that of real globular proteins.…”
Section: Model Interactions and Their Biophysical Basismentioning
confidence: 99%
“…14 Limited mutagenesis of small natural proteins populates alternate folds in certain cases, [15][16][17] and accumulation of simple mutations can lead to evolution of new folds. [17][18][19] Some modeling studies have found numerous close approaches or paths between different structures in sequence space [20][21][22][23] and even sequence ''supernetworks'' 24,25 that span many protein folds. In addition, sequences with two folds or functions may confer a fitness advantage under certain models of adaptive evolution.…”
Section: Introductionmentioning
confidence: 99%
“…H P polymers have been studied extensively as a model for the folding and evolution of proteins (51,(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73). Those studies show that unique folded structures can be encoded simply in the binary patterning of polar and hydrophobic residues, with finer tuning by specific interresidue contacts.…”
Section: "Flory Length Problem": Polymerization Processes Produce Mosmentioning
confidence: 99%